Paclobutrazol en la producción de biomasa e índice de cosecha del cultivo de maíz (Zea mays L.) sometido a una alta densidad de siembra - Machado García, Steven Stalyn (2022)
The present research was carried out at the University Campus "La María", property of the Quevedo State Technical University, and experimental plots of two hybrids and one variety of maize (Zea mays L.) were evaluated under the application of a growth inhibitor (Paclobutrazol). Six treatments were studied: T1 (Criollo without PBZ), T2 (Criollo with PBZ), T3 (Splendor without PBZ), T4 (Splendor with PBZ), T5 (Emblem without PBZ) and T6 (Emblem with PBZ), from a DCA with four replications. T